Community adaptation and climate change in the Northern Mountainous Region of Vietnam: A case study of ethnic minority people in Bac Kan Province. Issue 1 (2nd January 2020) - Son, Ho; Kingsbury, Aaron
ABSTRACT: Vietnam is highly vulnerable to climate change, and those most severely affected tend to be members of ethnic minority groups living in poverty in marginalized areas. This paper focuses on the Tay, Dao, and Hmong ethnic minorities the Northern Mountainous Region (NMR) of the country, and employs a mixed-method qualitative approach to assess their adaptation to a changing climate in the region as a case study. The NMR is the poorest area of Vietnam, and each of these ethnic minority groups was found to be both vulnerable and adapt in different ways. Results show that adaptation strategies faced considerable barriers, often directly influenced by gender, age, ethnicity, wealth, and location. Many locally-employed coping strategies were also found to be conditional on the strength and foresight (or futility and the lack of foresight) of institutions and policymakers on the local, regional, and central levels. While local knowledge and social capital did ease pressures, policy failures more typically led to mal-adaptation and welfare dependence. Improving not only the quality but also the focus of and access to government resources would considerably enhance the capacity for communities to adapt to the impacts of a changing climate.